Does Intra-Wound Vancomycin Powder Affect the Action of Intra-Articular Tranexamic Acid in Total Joint Replacement? - Koutalos, Antonios A. (Microorganisms, 2020)
The intra-articular use of tranexamic acid (TXA) has contributed to reduced blood loss in total joint arthroplasty (TJA). The purpose of this study is to assess the efficacy of simultaneously topical use of tranexamic acid and vancomycin powder within the TJA space. From 2016 to 2017, 219 consecutive total hip arthroplasties (THAs) and 272 total knee arthroplasties (TKAs) were performed in a tertiary care center, with a group of patients receiving intra-articular TXA and vancomycin, compared to patients receiving only TXA and to a control group that did not receive anything. Haemoglobin and hematocrit were measured preoperatively, on the first and third days. Transfusions and adverse events were recorded. Haemoglobin and hematocrit dropped significantly in all THA and TKA groups till the third day postoperatively, with a major reduction in the control group, compared to the other two treatment groups. Infections and thromboembolic events were similar in either group of the TJAs. In conclusion, the topical use of tranexamic acid mixed with the vancomycin powder within the joint space after the TJAs of the hip and knee did not alter the anti-fibrinolytic effect of TXA.